2009
DOI: 10.1007/s10452-009-9244-9
|View full text |Cite
|
Sign up to set email alerts
|

Home-field advantage: native signal crayfish (Pacifastacus leniusculus) out consume newly introduced crayfishes for invasive Chinese mystery snail (Bellamya chinensis)

Abstract: The introduction of non-indigenous plants, animals and pathogens is one of today's most pressing environmental challenges. Freshwater ecologists are challenged to predict the potential consequences of species invasions because many ecosystems increasingly support novel assemblages of native and nonnative species that are likely to interact in complex ways. In this study we evaluated how native signal crayfish (Pacifastacus leniusculus) and non-native red swamp crayfish (Procambarus clarkii) and northern crayfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 57 publications
(76 reference statements)
0
21
1
Order By: Relevance
“…A meta-analysis by Twardochleb et al (2013) showed consistently negative effects of crayfish on Gastropoda abundance and suggested a tendency for effects of nonnative species to be stronger than that of native species. However, the abundance and species richness of Sphaeriidae and Gastropoda did not differ between signal and noble crayfish lakes, and recent direct experimental comparisons indicate that effects can be either similar or different between species independent of species origin (Nyström et al 1999, Olden et al 2009, Haddaway et al 2012, Dorn 2013, Jackson et al 2014. Limited data are available on effects of crayfish on small Bivalvia in general (e.g., they were not included in the meta-analysis by Twardochleb et al 2013), but Klocker and Strayer (2004) found that the invasive species Orconectes rusticus and the native crayfish Orconectes limosus both fed readily and to the same extent on native bivalves (Sphaeriidae) in a laboratory experiment.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis by Twardochleb et al (2013) showed consistently negative effects of crayfish on Gastropoda abundance and suggested a tendency for effects of nonnative species to be stronger than that of native species. However, the abundance and species richness of Sphaeriidae and Gastropoda did not differ between signal and noble crayfish lakes, and recent direct experimental comparisons indicate that effects can be either similar or different between species independent of species origin (Nyström et al 1999, Olden et al 2009, Haddaway et al 2012, Dorn 2013, Jackson et al 2014. Limited data are available on effects of crayfish on small Bivalvia in general (e.g., they were not included in the meta-analysis by Twardochleb et al 2013), but Klocker and Strayer (2004) found that the invasive species Orconectes rusticus and the native crayfish Orconectes limosus both fed readily and to the same extent on native bivalves (Sphaeriidae) in a laboratory experiment.…”
Section: Discussionmentioning
confidence: 97%
“…These snails were introduced 40 years ago and are now broadly distributed in hundreds of lakes that historically supported relatively few native snails (Olden et al 2009). The Chinese mystery snail has now become a food source for both the native and invasive species of crayfish.…”
Section: Impactsmentioning
confidence: 99%
“…The Chinese mystery snail has now become a food source for both the native and invasive species of crayfish. Interestingly, the native crayfish is able to consistently handle and consume the snails at a faster pace, outcompeting both species of invasive crayfish for this novel food source (Olden et al 2009). Even so, the invasive red swamp crayfish still outnumbers the native signal crayfish by more than 2 to 1 where both species co-occur (Mueller 2007).…”
Section: Impactsmentioning
confidence: 99%
“…Mueller and Bodensteiner (2009) did not find competitive dominance of P. clarkii over native P. leniusculus under field conditions in a Washington lake. Olden et al (2009b) observed that P. clarkii was less predatory on an invasive snail common to Washington than P. leniusculus. More work on the distribution and impacts of this invader in the Pacific Northwest is needed.…”
Section: Red Swamp Crawfish (Procambarus Clarkii)mentioning
confidence: 95%